2021
DOI: 10.1093/scan/nsab007
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological models of emotion regulation: a meta-analysis of neuroimaging studies of acceptance as an emotion regulation strategy

Abstract: Emotional acceptance is an important emotion regulation strategy promoted by most psychotherapy approaches. We adopted the Activation Likelihood Estimation technique to obtain a quantitative summary of previous fMRI (functional Magnetic Resonance Imaging) studies of acceptance and test different hypotheses on its mechanisms of action. The main meta-analysis included 13 experiments contrasting acceptance to control conditions, yielding a total of 422 subjects and 170 foci of brain activity. Additionally, subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 84 publications
4
41
2
Order By: Relevance
“…Moreover, the IFG is linked to response inhibition (Aron et al, 2014 ) and may play an important role to block the behavioral expression of anger, or in other words, the externalization of anger. The dlPFC (including the SFG and the MFG) may be involved not only in reappraising the angry stimulus and eventually in implementing emotion regulation strategies (Buhle et al, 2014 ; Grecucci et al, 2013b , c ; Messina et al, 2021 ; Ochsner & Gross, 2005 ) but also in directly suppressing anger expression, as shown by tDCS studies in which the stimulation of the right dlPFC mitigates aggressiveness and negative emotional responses (Dambacher et al, 2015 ). The OFC is similarly involved in emotion regulation, but it seems to have a key role in anger control for its mediatory role in guiding insula’s activity when anger is experienced (Seok & Cheong, 2019 ; Sorella et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the IFG is linked to response inhibition (Aron et al, 2014 ) and may play an important role to block the behavioral expression of anger, or in other words, the externalization of anger. The dlPFC (including the SFG and the MFG) may be involved not only in reappraising the angry stimulus and eventually in implementing emotion regulation strategies (Buhle et al, 2014 ; Grecucci et al, 2013b , c ; Messina et al, 2021 ; Ochsner & Gross, 2005 ) but also in directly suppressing anger expression, as shown by tDCS studies in which the stimulation of the right dlPFC mitigates aggressiveness and negative emotional responses (Dambacher et al, 2015 ). The OFC is similarly involved in emotion regulation, but it seems to have a key role in anger control for its mediatory role in guiding insula’s activity when anger is experienced (Seok & Cheong, 2019 ; Sorella et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of the amygdala response by prefrontal functioning is a key feature of reappraisal (Buhle et al, 2014;Frank et al, 2014;Kohn et al, 2014). A meta-analysis revealed the absence of amygdala suppression during acceptance under explicit instructions, implying that mindful acceptance was independent of amygdala suppression (Messina et al, 2021). Previous studies of individual differences have revealed mixed results: the study that compared yoga mediators to controls supported the independence view by demonstrating an absence of the dlPFC-amygdala correlation (Froeliger et al, 2012); however, the study on Zen meditators showed larger deactivation in the amygdala of experts versus controls (Grant et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The neural correlates of the trait for adaptive emotion-focused coping have been investigated separately for reappraisal and acceptance, and the two lines of studies have reached different conclusions. The neural correlates of instructed, explicit use of these coping strategies have been studied extensively; recruitment of the prefrontal control system is involved in both reappraisal (Buhle et al, 2014;Frank et al, 2014;Kohn et al, 2014;Morawetz et al, 2017b) and acceptance (Messina et al, 2021), together with deactivation of the limbic system (e.g., amygdala) and the posterior cingulate cortex, respectively. The individual differences in the natural response to emotionally stressful stimuli depend on the different roles of the prefrontal executive system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical context, it provides greater clarity concerning the subcomponents existing before the correction of an error. This opens the way for neuropsychological treatment processes, whereby actions focus on stimulating the described executive functions within the rehabilitation process for those with frontal damage who have difficulties at this level [56][57][58]. From the theoretical perspective, this study presents a significant contribution, given that the body of research on executive functions is still developing in terms of its theoretical models [3].…”
Section: -Discussionmentioning
confidence: 99%